Vernal keratoconjunctivitis activity induces decrease of ocular surface CD14, TLR-4 and TLR-9 expression. Issue 4 (July 2022) - Sacchetti, Marta; Nebbioso, Marcella; Segatto, Marco; Abicca, Irene; Bruscolini, Alice; Zicari, Anna Maria; Lambiase, Alessandro
Purpose: CD14 is involved in the modulation of immune reaction via toll-like receptors (TLR) and may influence the development of allergic diseases. The role of CD14 in vernal keratoconjunctivitis (VKC) has not yet been investigated. The aim of this study is to evaluate changes of tear soluble sCD14 and conjunctival CD14, TLR-4 and 9 expression in patients with VKC in the active and quiescent phases. Methods: Eighteen patients with VKC during active inflammation (group A, N = 9), in the quiescent phase (group Q, N = 5) and after recovery (group R, N = 4) and 10 healthy subjects were included. Expression of sCD14 in tears and of CD14, TLR-4, and TLR-9 by conjunctival epithelium were evaluated by Western Blot in all groups. Results: Expression of tear sCD14 and of conjunctival CD14, TLR-4, and TLR-9 was significantly decreased in group A when compared with healthy subjects and with VKC group Q and R. Lower expression of sCD14, CD14, TLR-4, and TLR-9 were significantly correlated with the severity of papillary reaction, while the lower sCD14 was correlated with severity of conjunctival hyperemia. Conclusions: Tear sCD14, and conjunctival CD14, TLR4, and TLR-9 decreased during ocular surface inflammatory reaction in patients with VKC. CD14 and TLRs ocular surface evaluation may represent biomarkers of VKC activity and novel therapeutic target.